2012
DOI: 10.1021/jp212597y
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Radiation Induced Conformational Change and Hydrogen Atom Tunneling of 2-Chloropropionic Acid in Low-Temperature Ar Matrix

Abstract: Former assignments of the matrix-isolation infrared (MI-IR) spectrum of 2-chloropropionic acid are revised with the help of near-infrared (NIR) laser irradiation induced change in conformer ratios. This method allows not only the unambiguous assignment of each band in the MI-IR spectrum to the two trans (Z) and the cis (E) conformers but also the assignment of the spectral bands to different matrix sites. The tunneling decay of the higher-energy cis conformer prepared from both trans conformers in different si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 61 publications
3
42
0
2
Order By: Relevance
“…For several molecules containing a carboxylic group, and where high-energy conformers could be successfully produced in situ in cryogenic matrices by near-IR pumping of a lower energy precursor conformer, it has been observed that back-isomerization can take place spontaneously in the dark, by tunneling. 57,[66][67][68][69][70][71] In the present study, we have also investigated this possibility for TAA.…”
Section: Spontaneous Decay (By Tunneling) Of the High-energy Conformementioning
confidence: 99%
“…For several molecules containing a carboxylic group, and where high-energy conformers could be successfully produced in situ in cryogenic matrices by near-IR pumping of a lower energy precursor conformer, it has been observed that back-isomerization can take place spontaneously in the dark, by tunneling. 57,[66][67][68][69][70][71] In the present study, we have also investigated this possibility for TAA.…”
Section: Spontaneous Decay (By Tunneling) Of the High-energy Conformementioning
confidence: 99%
“…[175][176][177][178][179][180][181][182] These reactions are mostly carried out at cryogenic temperatures in noble gas or N 2 matrix environments.Itwas shown that such an environment can influence the tunneling rates of the isomerization reactions significantly.T his might be taken as ac aveat when comparing with, for example,q uantum chemical gas-phase calculations. [178,179,[183][184][185][186] In larger, bio-organic molecules,t unneling supports radical reactions such as in the autoxidation of tetraline. [187] Theregeneration of vitamin E(tocopherol) by ubiquinol was shown to be accelerated more than 4000 times by tunneling.…”
Section: Organic Chemistrymentioning
confidence: 99%
“…The quantum mechanical nature of the phenomenon is further underlined by a significant influence of isotopic substitution on the rate of conversion, which is by orders of magnitude slower, but not halted entirely, in the corresponding O-d-carboxylic acids. [7][8][9][10]13,14,33,34 Numerous examples of QMT in carboxylic acids have been found in recent years (Scheme 1), the most prominent being 4,6,10,[12][13][14][15][16]21,22,24,26,28,30,32 acetic (1b), 5,7,8,10,15,21,28 propionic (1c), 9,21,28,29 S(−)-2-chloropropionic (1d), 25 as well as propiolic acid (1e) 31 and the aromatic meta-chlorobenzoic acid (2) along with variously para-substituted benzoic acid derivatives (3a−f). 20,23 Remarkably, spectral proof for the existence of the monomeric (E)-isomer of 3 and several of its para-substituted derivatives was provided only in 2010.…”
Section: ■ Introductionmentioning
confidence: 99%